Realization apoptosis in nucleus sincythiotrophoblast villus of placenta at pregnant, transferred an aggravation of a herpes-virus infection depending on thecontents in homogenate placentae anneexin V - M. T. Lutsenko; I. A. Andriyevskaya (Бюллетень сибирской медицины)
The reason of increase apoptosis in sincythiotrophoblast is suppression of activity ATP-ase, moving phosphatydilserin on an external membrane sincythiotrophoblast, and increase of quantity annexin V in homogenate placentae.